2020
DOI: 10.1080/23322373.2020.1779450
|View full text |Cite|
|
Sign up to set email alerts
|

A business case argument for corporate social responsibility disclosure in Nigeria

Abstract: From the theoretical perspectives of stakeholder, agency and slack resources, and using fixed effects and random effects models, this study investigates the relationship between Corporate Social Responsibility (CSR) and financial performance. The study adopts fixed and random effects panel estimates which deal with unobserved heterogeneity not addressed by OLS. The result is positive between CSR and Tobin's q. This strengthens the argument that CSR creates value for stakeholders. The implications of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, the results of some studies indicate that the influence of stakeholders on firm value has not been adequately investigated [106]. On the other hand, some studies show that the high firm value resulting from the company's implementation of its social responsibilities adds positive value to stakeholders [144]. This cluster came in the last classification, and Figure 13 shows the presence of several other interconnected words, such as carbon emissions, accountability, and transparency.…”
Section: Stakeholder Clustermentioning
confidence: 99%
“…However, the results of some studies indicate that the influence of stakeholders on firm value has not been adequately investigated [106]. On the other hand, some studies show that the high firm value resulting from the company's implementation of its social responsibilities adds positive value to stakeholders [144]. This cluster came in the last classification, and Figure 13 shows the presence of several other interconnected words, such as carbon emissions, accountability, and transparency.…”
Section: Stakeholder Clustermentioning
confidence: 99%
“…For example, the influence of higher disclosure practices on firm performance is inconclusive in the literature. Some studies reported that sustainability disclosure is positively linked with firm performance (Adams et al, 2022; Chijoke‐Mgbame & Mgbame, 2018; Ode‐Ichakpa et al, 2020; Ofori et al, 2014; Siueia et al, 2019), and firm valuation (De Klerk & De Villiers, 2012; Thompson et al, 2022), indicating the growing moral obligation to society, and strategic activity geared at securing legitimacy from the society influence the sustainability practice.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Nonetheless, these studies are too fragmented to constitute an intellectual corpus. For instance, despite the increasing concerns over environmental problems in Africa arising from corporate actions (Iredele, 2020; Ode‐Ichakpa et al, 2020), a holistic understanding of the extent and quality of sustainability reporting in the region does not exist. Therefore, the role of firms in the sustainable development of the continent is still less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…With realities of competition amongst manufacturing firms, financial performance is important to translate firms into successful performers [32], [40], [42], [43], [55], [60]. Accordingly, scholars and management continuously look for viable strategies to sustain their profits.…”
Section: Literature and Hypothesismentioning
confidence: 99%